Antimicrobials in global salmon farming: Resistance, effect on human health and the environment, and future perspectives (Scientia Agropecuaria, 2024)
Salmon farming in the face of antimicrobial resistance and effects on human health and environment. Abstract: The present review compiles and analyzes studies of the last five years on antibiotic use in the salmon industry, reported effects on fish and humans, and impacts on the environment. There is a growing concern regarding the current management of veterinary therapeutic plans used for the treatment and control of bacterial infections. The main problems are related to the increase of resistance to antibiotics by pathogenic and non-pathogenic bacteria communities, horizontal transfer of resistance genes between bacterial cells, and a major number of cases of failed medical treatments in human and animal populations. Therefore, the challenges for the future will be to reduce dependence on antibiotics in animal production through research into alternatives technologies, the collection of epidemiological information from productive sectors that allow detailed monitoring in the different cultivation phases, biosafety measures from an approach of One Health, and strict supervision in the formulation of medicines by professionals in the animal area.
Keywords: antimicrobials; salmon farming; resistance mechanisms; microbiota; marine sediment